Controlling microsegregation–induced phase formation and pitting corrosion in wire-arc additively manufactured precipitation-hardened martensitic stainless steel - Mozumder, Yahya H.; Taylor, Mark; Bongiorno, Vincenzo; Lu, Yao; Wang, Jun; Williams, Stewart W.; Prangnell, Philip B.; Pickering, Ed J.; Scenini, Fabio (Elsevier, 2026)
Wire-arc additive manufacturing (WAAM) often leads to elemental microsegregation and non-equilibrium phase formation during solidification, which can compromise the corrosion performance of alloys. This study presents the first detailed investigation of WAAM processed Custom 465® (C465), a precipitation-hardened martensitic stainless steel, focusing on the effect of post-printing heat treatment strategies on the microstructure and its pitting corrosion behaviour, benchmarked against the conventionally manufactured wrought C465 material. As-printed C465 exhibited large columnar prior austenite grains (PAGs) and pronounced microsegregation, which stabilised the retained austenite and Laves phases. The standard solution treatment (SST) refined the PAGs but was insufficient to eliminate microsegregation. Guided by diffusion-controlled transformation (DICTRA) simulations, a suitable homogenisation treatment was developed that effectively reduced WAAM-induced microsegregation and associated secondary phases. Ageing treatment after the SST only partially promoted martensite-to-austenite reversion, likely driven by pre-existing retained austenite and Ni-segregation. In contrast, ageing treatment after homogenisation and SST largely suppressed this transformation, resulting in a microstructure comparable to the wrought counterpart. The corrosion performance of C465 produced by both WAAM and conventional routes was further evaluated using cyclic potentiodynamic polarisation and electrochemical noise techniques. With the standard heat treatment, the WAAM material exhibited inferior pitting resistance compared to its wrought counterpart. Surface characterisation following anodic polarisation revealed pit initiation at Cr-depleted interdendritic retained austenite regions and Laves/matrix interfaces in the WAAM material. However, homogenisation prior to SST and ageing treatment significantly enhanced the pitting resistance by eliminating preferential pit nucleation sites, thereby achieving a performance comparable to the wrought counterpart. Overall, this work demonstrates the critical role of post-printing heat treatment strategies in addressing WAAM-induced microstructural heterogeneities and mitigating pitting susceptibilities.
Keywords: 40 Engineering; 4014 Manufacturing engineering; 4016 Materials engineering; Wire-arc additive manufacturing; Custom 465®; Martensitic stainless steel; Microsegregation; Homogenisation; Pitting resistance